Stable isotope (δ13C and δ18O) of Plio/Pleistocene benthic foraminifers of piston core SO213/1_1-2 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler; Thomas A Ronge (PANGAEA, 2025)
Sediment cores from the South Pacific (Chile Fracture Zone) obtained during RV SONNE cruise SO213 (SOPATRA) in December 2011 allow us to reconstruct lateral changes in the subpolar gyres in the pelagic South Pacific over the last ~4.8 million years. This dataset comprises benthic stable carbon (δ13C) and oxygen isotope (δ18O) data from piston core SO213_01-2, which was recovered from the South Pacific (36°13.17 S 85°01.56 W) from 2809 m water depth. Measurements were performed on the benthic foraminiferal species Uvigerina peregrina. Sampling and analytical studies were carried out from 0.005–12.745 m core depth at ~2-4 cm spatial resolution. The isotope analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV carbonate preparation device.